Prolonged sitting: Is it a distinct coronary heart disease risk factor? - Dunstan, D.; Thorp, A.; Healy, Genevieve (2011)
Purpose of Review: Prolonged sitting (sedentary behavior) has deleterious cardiovascular and metabolic correlates; however, little is known about the associations of too much sitting with all-cause and cardiovascular mortality risk. In addition to the adverse effects of total sitting time, the manner in which it is accumulated has also been postulated to be important for cardiovascular health. Recent Findings: We describe recent evidence from several research papers published in the last 12-18 months, showing deleterious relationships of sedentary behavior with mortality outcomes. We also explore emerging findings on breaking up sedentary time and its potential beneficial impact on cardiovascular health. Summary: Consistent independent associations have been observed between sitting time/sedentary behaviors and elevated all-cause and cardiovascular disease mortality risk. Generally, these associations have persisted following adjustment for physical activity. Furthermore, total sedentary time (measured objectively via accelerometer) is detrimentally associated with several cardiovascular risk factors, whereas breaking up sedentary time (independent of total sedentary time and moderate-to-vigorous intensity activity) is beneficially associated. This evidence provides further support to the importance of avoiding prolonged, uninterrupted periods of sitting time for cardiovascular health. However, further evidence from intervention trials is required to establish the causal pathways.